Multiple waves of freshwater colonization of the three-spined stickleback in the Japanese Archipelago - Kakioka, Ryo (BMC Evol Biol, 2020)
BACKGROUND: The three-spined stickleback (Gasterosteus aculeatus) is a remarkable system to study the genetic mechanisms underlying parallel evolution during the transition from marine to freshwater habitats. Although the majority of previous studies on the parallel evolution of sticklebacks have mainly focused on postglacial freshwater populations in the Pacific Northwest of North America and northern Europe, we recently use Japanese stickleback populations for investigating shared and unique features of adaptation and speciation between geographically distant populations. However, we currently lack a comprehensive phylogeny of the Japanese three-spined sticklebacks, despite the fact that a good phylogeny is essential for any evolutionary and ecological studies. Here, we conducted a phylogenomic analysis of the three-spined stickleback in the Japanese Archipelago. RESULTS: We found that freshwater colonization occurred in multiple waves, each of which may reflect different interglacial isolations. Some of the oldest freshwater populations from the central regions of the mainland of Japan (hariyo populations) were estimated to colonize freshwater approximately 170,000 years ago. The next wave of colonization likely occurred approximately 100,000 years ago. The inferred origins of several human-introduced populations showed that introduction occurred mainly from nearby habitats. We also found a new habitat of the three-spined stickleback sympatric with the Japan Sea stickleback (Gasterosteus nipponicus). CONCLUSIONS: These Japanese stickleback systems differ from those in the Pacific Northwest of North America and northern Europe in terms of divergence time and history. Stickleback populations in the Japanese Archipelago offer valuable opportunities to study diverse evolutionary processes in historical and contemporary timescales.